Title in English Incentives and their relationship to the behavior of citizenship among the staff of the youth and sports directorates - triche.lahcen (sports creativity, 2025)
The study aimed to determine the correlation between material and moral incentives in the behavior of organizational citizenship in a sample of the staff of the youth and sports directorates. The researcher used the descriptive method in the method of interrelationships and the questionnaire as a tool for collecting data and information. The sample of the study (75) employees and employees distributed in three states Msila, Batna, Djalfa, and the researcher found that it There is a correlation between the material incentives and the behavior of organizational citizenship among the staff of the youth and sports directorates There is a correlation between moral incentives and organizational citizenship behavior among the staff of youth and sports directorates